Physicochemical quality of cauliflower as influenced by cling film wrapping during storage - Nasrin, Taslima Ayesha Aktar; Islam, Md Nazrul; Rahman, Md Atiqur; Arfin, Most Sadia; Afroz, Mafruha; Molla, Mohhammad Mainuddin; Sabuz, Ashfak Ahmed; Matin, Md Abdul (International Journal of Agricultural Research, Innovation and Technology, 2023)
Compact, medium size, white to creamy cauliflower curds were packed into different packaging techniques like i. without packaging (control); ii. packed in low density polyethylene (LDPE) bag with 1% perforation; iii. wrapped with polyethylene (PE) cling film and iv. newspaper (locally used). Half of each treatment was kept at (6±1°C and 50±5% RH) and the other half was kept at ambient conditions (25±3°C and 60±5% RH). LDPE bag or PE cling film has a great effect to retain firmness and reduce weight loss of cauliflower in both storage conditions. Respiration rate, rot incidence and changes of colour values (lightness and hue angle) was reduced significantly for the cauliflowers packed in LDPE bag or wrapped with PE cling film stored in a refrigerator than that of control (without packaging) and all packaging techniques stored at ambient condition throughout the storage period. Initially, acidity, TSS and ascorbic acid content were 0.26%, 4.7° Brix and 58.7 mg 100g-1, respectively. Ascorbic acid content was reduced severely in the cauliflower stored in ambient conditions than that stored in a refrigerator. Cauliflower wrapped with PE cling film and packed in an LDPE bag (1% perforation) stored in a refrigerator (6±1°C and 50±5% RH) could retain white colour, good sensory quality, firm and fresh curds with minimum loss in weight, texture and disease incidence up to 18 days and 16 days, respectively. Int. J. Agril. Res. Innov. Tech. 12(2): 155-163, December 2022